Managing People with Diabetes Fasting for Ramadan During the COVID‐19 Pandemic: A South Asian Health Foundation Update. Issue 7 (5th June 2020) - Hanif, S.; Ali, S. N.; Hassanein, M.; Khunti, K.; Hanif, W.
Abstract: The month of Ramadan forms one of the five pillars of the Muslim faith. Adult Muslims are obligated to keep daily fasts from dawn to sunset, with exceptions. This year Ramadan is due to begin on 23 April 2020 and the longest fast in the UK will be approximately 18 hours in length. In addition, due to the often high‐calorie meals eaten to break the fast, Ramadan should be seen as a cycle of fasting and feasting. Ramadan fasting can impact those with diabetes, increasing the risk of hypoglycaemia, hyperglycaemia and dehydration. This year, Ramadan will occur during the global COVID‐19 pandemic. Reports show that diabetes appears to be a risk factor for more severe disease with COVID‐19. In addition, the UK experience has shown diabetes and COVID‐19 is associated with dehydration, starvation ketosis, diabetic ketoacidosis and hyperosmolar hyperglycaemic state. This makes fasting in Ramadan particularly challenging for those Muslims with diabetes. Here, we discuss the implications of fasting in Ramadan during the COVID‐19 pandemic and make recommendations for those with diabetes who wish to fast. Novelty Statement: Guidelines about managing diabetes during Ramadan have been published by various societies, including the latest one from the South Asian Health Foundation UK. The COVID‐19 pandemic poses new challenges for managing people with diabetes who choose to fast during Ramadan. These guidelines address these challenges and give the most up to date advice based on current evidence, to help those who choose to fast do so safely.